The individual taxpayer utility function with tax optimization and fiscal fraud environment - Paweł Pankiewicz (e-Finanse: Financial Internet Quarterly, 2011)
In this paper I examine a taxpayer utility function determined by the extended set of variables - i.e. consumption, labor and tax-evasion propensity. This constitutes the main framework for the analysis of taxpayer's decision making process under assumption that in the economy there exist two main reduction methods: a) access to tax optimization techniques, which may decrease effective tax burden and are fully compliant with binding laws, but generate transactional costs and 2) possibility of fiscal fraud in particular tax evasion, as the alternative method of reducing tax due, which has no direct transactional costs, but involves tax litigation risk.
Keywords: H21; H26; 330; taxation theory; taxpayer utility; tax evasion